Factors associated with consistent contraception and condom use among Māori secondary school students in New Zealand. (27th December 2013) - Clark, Terryann C; Crengle, Sue; Sheridan, Janie; Rowe, Deborah; Robinson, Elizabeth
<x xml:space="preserve">Abstract</x> Aims The aims of this study are to provide a profile of sexual health behaviours of Māori youth and to identify factors associated with consistent condom and contraception use. Methods Multivariable analyses were conducted to determine relationships between consistent contraception and condom use among all 2059 sexually active Māori participants in the 2007 New Zealand youth health and well‐being survey of secondary school students. Results Forty per cent of Māori students were currently sexually active; of these, 55.3% always used contraception, and 41.1% always used condoms. Risk factors for not using contraception were less than or equal to three sexual partners (males odds ratio (OR) 0.55, P = 0.04, females OR 0.35, P = 0.04) and regular cigarette use for females (OR 0.52, P = 0.02). Risk factors for not using condoms were 13‐ to 15‐year‐old females (OR 1.95, P < 0.01) and females who enjoyed sex (OR 0.52, P = 0.02). Family connection was associated with increased use of condoms among males (OR 1.07, P < 0.01). Conclusions Reducing sexual risks, increasing opportunities for healthy youth development and family connectedness, alongside access to appropriate services, are required to improve the sexual health of Māori youth.